PEPPER CUTTING GROWTH RESPONSE ON THE USE OF VARIOUS MANURE ON RED YELLOW PODSOLIC SOIL - Subroto, Warganda, Rini Susana, Agus (Fakultas Pertanian Universitas Tanjungpura, 2019)
Increasing the productivity of red yellow podsolic soil to increase the growth of pepper cuttings include the provision of organic material in the form of manure. The research aims to determine the growth response of pepper cutting to the provision of several types of manure and determine the best kind of manure for the growth of pepper cuttings on red yellow podsolic. The research was conducted in Bansir Laut Village, Pontianak City, starting May 25th, 2018 until August 25th, 2018. The method used in this study is a field experiment method with a completely randomized design pattern (CRD) consisting of 4 treatments and 5 replications, each replication consisting of 5 sample plants, media comparisons using a volume ratio (v / v). The treatment is as follows: m1 = Soil: Cow manure, m2 = Soil : Chicken manure, m3 = Soil: Duck Manure and m4 = Soil: Quail Manure. The variables observed in this study were the number of roots, root length, root volume, root dry weight, number of leaves, shoot dry weight and percentage of live. Based on the results of the study it can be concluded that, the use of several types of manure has no significant effect on all observation variables, but provides the growth of pepper cuttings that are equally good for all observed variables. Keywords: manure, pepper, red yellow podsolic Increasing the productivity of red yellow podsolic soil to increase the growth of pepper cuttings include the provision of organic material in the form of manure. The research aims to determine the growth response of pepper cutting to the provision of several types of manure and determine the best kind of manure for the growth of pepper cuttings on red yellow podsolic. The research was conducted in Bansir Laut Village, Pontianak City, starting May 25th, 2018 until August 25th, 2018. The method used in this study is a field experiment method with a completely randomized design pattern (CRD) consisting of 4 treatments and 5 replications, each replication consisting of 5 sample plants, media comparisons using a volume ratio (v / v). The treatment is as follows: m1 = Soil: Cow manure, m2 = Soil : Chicken manure, m3 = Soil: Duck Manure and m4 = Soil: Quail Manure. The variables observed in this study were the number of roots, root length, root volume, root dry weight, number of leaves, shoot dry weight and percentage of live. Based on the results of the study it can be concluded that, the use of several types of manure has no significant effect on all observation variables, but provides the growth of pepper cuttings that are equally good for all observed variables. Keywords:manure, pepper, red yellow podsolic